Zao čas u verovanju slovenskih naroda «Neroven», «lih čas» v pover’jah slavjanskih narodov - Radenković, Ljubinko (Studia mythologica Slavica, 2011)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">According to the Slavic beliefs, during the circulation of the time, at the shift between the night and the day, there is a dangerous interlude, when the man is exposed to the possibility of misfortunate accident or even death. If we imagine the time as the current that flows in from the daybreak till noon, and than flows out from the noon till late at night, than each stop along that route presents a “crack”, an entrance to the world beyond.